Exploring RAB11A Pathway to Hinder Chronic Myeloid Leukemia-Induced Angiogenesis In Vivo - Catarina Roma-Rodrigues; Alexandra R. Fernandes; Pedro V. Baptista (Pharmaceutics, 2023)
Neoangiogenesis is generally correlated with poor prognosis, due to the promotion of cancer cell growth, invasion and metastasis. The progression of chronic myeloid leukemia (CML) is frequently associated with an increased vascular density in bone marrow. From a molecular point of view, the small GTP-binding protein Rab11a, involved in the endosomal slow recycling pathway, has been shown to play a crucial role for the neoangiogenic process at the bone marrow of CML patients, by controlling the secretion of exosomes by CML cells, and by regulating the recycling of vascular endothelial factor receptors. The angiogenic potential of exosomes secreted by the CML cell line K562 has been previously observed using the chorioallantoic membrane (CAM) model. Herein, gold nanoparticles (AuNPs) were functionalized with an anti-RAB11A oligonucleotide (AuNP@RAB11A) to downregulate RAB11A mRNA in K562 cell line which showed a 40% silencing of the mRNA after 6 h and 14% silencing of the protein after 12 h. Then, using the in vivo CAM model, these exosomes secreted by AuNP@RAB11A incubated K562 did not present the angiogenic potential of those secreted from untreated K562 cells. These results demonstrate the relevance of Rab11 for the neoangiogenesis mediated by tumor exosomes, whose deleterious effect may be counteracted via targeted silencing of these crucial genes; thus, decreasing the number of pro-tumoral exosomes at the tumor microenvironment.